2007
DOI: 10.1007/s10532-007-9170-2
|View full text |Cite
|
Sign up to set email alerts
|

N-demethylation of neonicotinoid insecticide acetamiprid by bacterium Stenotrophomonas maltophilia CGMCC 1.1788

Abstract: Our previous study found that Stenotrophomonas maltophilia CGMCC 1.1788 could hydroxylate imidacloprid (IMI) to 5-hydroxy IMI. Here we first report that S. maltophilia CGMCC 1.1788 can demethylate acetamiprid (AAP) to form IM 2-1 that was characterized by HPLC-MS/MS and NMR. IM 2-1 retained only 10.5% contact activity and 13.1% oral activity of AAP against horsebean aphid. Time course of biotransformation under existing of sucrose revealed that 58.9% of AAP disappeared, but only 16.7% of reduced AAP was transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 17 publications
4
46
0
Order By: Relevance
“…Stenotrophomonas maltophilia GGMCCL.1788 hydroxylates IMI in the 5-position 41 and THI in the 4-position 42 and N-demethylates ACE. 43 Pseudomonas sp.1G converts IMI and TMX to their N-nitrosoguanidine, guanidine, and N-carbamoylimine metabolites. 44 Rhodotorula mucilaginosa strain IM-2 converts ACE to the N-acetyl derivative of 6-chloropyridinyl-3-methylamine and hydrolyzes THI to the corresponding Journal of Agricultural and Food Chemistry ARTICLE N-carbamoylimine.…”
Section: ' Compounds and Substituentsmentioning
confidence: 99%
“…Stenotrophomonas maltophilia GGMCCL.1788 hydroxylates IMI in the 5-position 41 and THI in the 4-position 42 and N-demethylates ACE. 43 Pseudomonas sp.1G converts IMI and TMX to their N-nitrosoguanidine, guanidine, and N-carbamoylimine metabolites. 44 Rhodotorula mucilaginosa strain IM-2 converts ACE to the N-acetyl derivative of 6-chloropyridinyl-3-methylamine and hydrolyzes THI to the corresponding Journal of Agricultural and Food Chemistry ARTICLE N-carbamoylimine.…”
Section: ' Compounds and Substituentsmentioning
confidence: 99%
“…20 The bacterium Stenotrophomonas maltophilia CGMCC 1.1788 degraded AAP via N-demethylation to form IM 2-1. 21 In a previous study, we reported that the plant growth-promoting rhizobacterium Variovorax boronicumulans CGMCC 4969 degraded thiacloprid to its amide metabolite and the carcinogen acrylamide to acrylic acid. 22,23 Bacteria belonging to the genus Variovorax are common inhabitants of water and soil.…”
Section: Introductionmentioning
confidence: 97%
“…Bioassay showed that the hydroxylation by S. maltophilia and decyanotation of 4-hydroxy thiacloprid are dramatic detoxic process, and the Ndemethylation of acetamiprid is ten times lower detoxicity (Chen et al 2008), while the hydroxylation of imidacloprid and subsequent elimination of water to form olefin imidacloprid are ten times increasing Fig. 4 Inhibition of PBO on the hydroxylation of thiacloprid by resting cells of S. maltophilia.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding and contact bioassay against horsebean aphid Aphis craccivora was tested by the method described by Nauen (1999) and our previous study (Chen et al 2008) at the National Pesticide Research & Development South Centre, Nanjing. Bioassay was replicated three times, the number of pest exceeded 30 in each dependant experiment, and the total number of pest was more than 100.…”
Section: Bioassays Of Metabolites Of Thiaclopridmentioning
confidence: 99%
See 1 more Smart Citation